Essay Writing Strategies Employed by English-Majored Sophomores at A University in Vietnam - Nguyen, Trang (International Journal of Language and Literary Studies, 2024)
This study investigates students’ use of essay writing strategies in different stages of the writing process. The participants included 105 English-majored sophomores at Hanoi Law University who have completed two courses in paragraph and essay writing instruction. A 5-level Likert close-ended survey questionnaire was designed to collect quantitative data regarding students’ frequency of applying overall and specific writing strategies in pre-writing, while-writing, and post-writing stages. The results revealed that while-writing strategies were used at high frequency by the participants while pre-writing and post-writing strategies were used at medium frequency. It is also found that, at the pre-writing stage, the students prefer reading sample essays; trying to understand the task requirements by either referring to their teacher’s notes or discussing with their teachers and friends and having a mental, unwritten plan before writing. While writing, students have taken use of various strategies which can be grouped into strategies to deal with the structure of the essay, strategies to develop ideas, strategies to activate vocabulary use, and strategies to review their mechanics. The strategies in the post-writing stage are the least frequently used, which include reading the whole text silently, checking if the essay matches the requirements, then making changes in the spelling and punctuation. Revising following their teacher’s feedback and actively asking their teacher or classmates are also frequently applied techniques for essay writing revision.